1991
DOI: 10.1073/pnas.88.24.11315
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the cholinesterase gene by Alu insertion: possible mechanism for human gene transposition.

Abstract: The human cholinesterase (ChE) gene from a patient with acholinesterasemia was cloned and analyzed. By using ChE cDNA as a probe, four independent clones were isolated from a genomic library constructed from the patient's DNA. Sequencing analysis ofall of the four clones revealed that exon 2 of the ChE gene was disrupted by a 342-base-pair (bp) insertion of Alu element, including a poly(A) tract of 38 bp, which showed 93% sequence homology with a current type of human Alu consensus sequence. Southern blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
1
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(68 citation statements)
references
References 17 publications
2
63
1
2
Order By: Relevance
“…been described: one in the promoter region (42) and the other one occurred in exon 2 leading to gene inactivation and a silent phenotype in a Japanese family (43). A short interspersed element was also found in the rabbit BChE intron 2 (44 .…”
Section: Discussionmentioning
confidence: 93%
“…been described: one in the promoter region (42) and the other one occurred in exon 2 leading to gene inactivation and a silent phenotype in a Japanese family (43). A short interspersed element was also found in the rabbit BChE intron 2 (44 .…”
Section: Discussionmentioning
confidence: 93%
“…The great majority of Alu repeats in human DNA were fixed in an ancestral primate genome before the emergence of the human lineage (reviewed in reference 40). Although Alu retroposition indeed occurs in humans (16,35,46,48), the available data indicate that (i) certain Alu sequences have been more prolific than others and (ii) the rate of new Alu insertions into the genome has declined during recent periods of primate evolution (6,40,41).…”
mentioning
confidence: 99%
“…The great majority of Alu repeats in human DNA were fixed in an ancestral primate genome before the emergence of the human lineage (reviewed in reference 40). Although Alu retroposition indeed occurs in humans (16,35,46,48), the available data indicate that (i) certain Alu sequences have been more prolific than others and (ii) the rate of new Alu insertions into the genome has declined during recent periods of primate evolution (6,40,41).The Alu retroposons that were actively proliferating during ancient, intermediate, and modern evolutionary times are reflected by three subfamilies of Alu sequences that remain distinguishable in human DNA (7,23,38,44,50; reviewed in references 40 and 41). The subfamily consensus sequence referred to as Alu Sx (formerly PS and Major; see nomenclature in reference 2) represents the sequence that produced approximately 85% of the Alus in the human genome 60 to 30 million years ago.…”
mentioning
confidence: 99%
“…The majority of the human AluYb elements integrated into the genome during the last 3 to 4 million years (Myr) and reached a total copy number of about 2000 elements . The human diseases caused by de novo AluYb8 insertions suggest that this subfamily is currently actively retrotransposing, and a comprehensive analysis of themorphic in human genome (Muratani et al 1991;Oldridge et al 1999;Carter et al 2004). Previous studies suggested that the evolutionary history of the AluYb lineage is much older than its period of major expansion in the human genome, and AluYb elements have also been identified in other nonhuman primates (Zietkiewicz et al 1994;Gibbons et al 2004).…”
mentioning
confidence: 99%